2012
DOI: 10.3937/kampomed.63.229
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Study on Enhanced Cognitive Function with Acupuncture and Improvements in Life Style

Abstract: Since it is supposed that the number of patients with dementia will increase as populations age in the near future, it is important to prevent dementia. In the present study, we examined whether acupuncture and life style improvements are able to enhance cognitive function.The subjects who worry about being forgetful were recruited and divided at random into two groups ; a group receiving acupuncture with transcutaneous electrical acupuncture-point stimulation (TEAS) and improvements in life style (20 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In those studies, acupuncture was found to be more effective in patients with some types of pain, compared with those who did not receive any treatment. Yamazaki et al 7 showed that acupuncture could enhance cognitive function and possibly prevent dementia. In 1999, Guidelines on basic training and safety in acupuncture was published by the World Health Organization, 8 and the therapy has been approved for treatment of various diseases including diseases of the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…In those studies, acupuncture was found to be more effective in patients with some types of pain, compared with those who did not receive any treatment. Yamazaki et al 7 showed that acupuncture could enhance cognitive function and possibly prevent dementia. In 1999, Guidelines on basic training and safety in acupuncture was published by the World Health Organization, 8 and the therapy has been approved for treatment of various diseases including diseases of the nervous system.…”
Section: Introductionmentioning
confidence: 99%